Factors that Influence the Implementation of Hospital Management Information Systems on the Performance of Registration Officers at RSU Bandung Medan - Sapriadi, Sapriadi; Zega, Leli Martini (Journal La Medihealtico, 2023)
The Hospital Management Information System used in a hospital must provide operational convenience and must be able to overcome obstacles to patient service in the hospital. The importance of SIMRS was strengthened by the enactment of Law Number 44 of 2009 concerning Hospitals which states that every hospital is obliged to record and report all activities of hospital administrators in the form of SIMRS. The aim of this research is to determine the factors that influence the implementation of a hospital management information system on the performance of registration officers at the Bandung Medan General Hospital in 2023. This research method uses descriptive qualitative methods. The research was conducted at RSU Bandung Medan in 2023. The informants in this research were 1 triangulation informant, 2 main informants, 1 additional informant. Data collection methods use interviews, observation and documentation methods. The research results of the computer hardware factors used are sufficient for the registration officer's needs, the software still has system failures in the application due to the absence of routine maintenance on the SIMRS application, the officer's brainware still has not received formal training, the SIMRS implementation procedure is in accordance with Standard Operating Procedures ( SOP) that applies, the Communication Network has problems with the network used, such as a network that is still unstable. Research shows that there is an influence of hardware, software, brainware, procedures, communication network factors on the performance of registration officers. It is hoped that sufficient equipment can support all the work of officers, routine maintenance is carried out on applications, official training is held for officers, officers can carry out their duties in accordance with Standard Operating Procedures (SOP), network maintenance.